Transcriptome analysis and bioinformatic mining of microsatellite and SNP markers from ests of the eastern oyster, Crassostrea Virginica (Gmelin, 1791) - Quilang, Jonas P.
The eastern oyster, Crassostrea virginica (Gmelin, 1791), is an economically important species as it is being harvested extensively and cultured in many areas in North America. It is also ecologically important because natural populations of this species form oyster reefs which serve as vital components of estuarine ecosystems. Populations of C. virginica have been threatened by overfishing, habitat degradation, and by the devastating effects of diseases. A few expressed sequence tags (ESTs) have been generated from this species, but these came from small-scale studies using limited kinds of tissues for the construction of cDNA libraries. Efficient generation of ESTs from this species has also been hindered by a high redundancy of mtDNA transcripts. Thus, to obtain a broader coverage of the transcriptome of this organism, a normalized and subtracted C. virginica cDNA library was constructed from pooled RNA isolated from hemocytes, mantle, gill, gonad and digestive tract, muscle, and whole juvenile. A total of 6,528 clones were sequenced from this library and after removal of vector, adapter, and polyA tail and exclusion of ESTs shorter than 100 bp, 5,542 high-quality sequences were obtained with an average length of 473 bp. Contig assembly yielded 635 contigs and 4,053 singletons giving a total of 4,688 unique sequences. This represented an 85% discovery rate or 15% redundancy rate suggesting that gene discovery from this library is efficient. About 46 % (2,174) of the unique ESTs had significant hits (E value ≤ 1e-05) in the non-redundant protein database; 1,104 of which were annotated using Gene Ontology (GO) terms for biological process, molecular function, and cellular component. The 4,688 unique sequences obtained from this study were also searched against the ESTs for C. virginica in dbEST using BLASTN and 3,787 (81%) were found to be novel C. virginica ESTs. A total of 35 microsatellites were identified from the ESTs generated; 18 of which have sufficient flanking sequences for primer design. A total of 6,533 putative SNPs were also identified using all existing C. virginica ESTs in public databases and the newly generated ESTs. Cluster analysis of the 9,018 C. virginica ESTs existing in public databases and the 5,542 ESTs generated from this study resulted in 8,444 unique sequences (1,606 contigs and 6,838 singletons), 3,767 of which had significant hits to the non-redundant protein database. These ESTs as well as the putative SNPs and microsatellites that were identified in this study provide valuable genome resources for marker validation, genetic linkage and QTL analysis, future microarray development, and gene characterizations in this species.